Rumen Fermentation Quality and Invitro Digestibility of Palm Frond Silage With The Addition of Tofu Pulp and Corn Bran - Harahap, Anwar Efendi; Mucra, Dewi Ananda; Sepriadi, Sigit; Harianti, Fitri (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2025)
Palm frond leaves have the potential to be used as ruminant feed in the form of silage with the addition of tofu and corn pulp flour as an effort to improve the quality of silage products. The purpose of the study was to assess the fermentation quality and invitro digestibility of palm frond silage supplemented with tofu and corn bagasse flour. This study used a completely randomized design (CRD) method with 4 treatments and 5 replicates arranged, namely: P0 = 100% palm fronds; P1 = 100% palm fronds + 5% molasses; P2 = 100% palm fronds + 5% tofu pulp + 5% corn f bran + 5% molasses; P3 = 100% palm fronds + 10% tofu pulp + 10% corn bran + 5% molasses and P4 = 100% palm fronds + 15% tofu pulp + 15% corn bran + 5% molasses. Parameters observed included NH3 production (mM), total VFA (mM), DMD (%) and DMO (%). The results showed that supplementation of tofu dregs flour and corn flour with various proportions affected the rumen fermentation value and invitro digestibility (P<0.05) of palm frond silage. The higher the addition of tofu dregs flour and corn bran had an effect on increasing rumen fermentability and overall invitro digestibility. The conclusion of this research is that treatment P4 = 100% palm fronds + 15% tofu dregs + 15% corn bran + 5% molasses is able to improve the quality of rumen fermentation and invitro digestibility of palm frond silage